Solve for \( y \). \[ 2 y^{2}+11 y+5=(y+5)^{2} \] If there is more than one solution, separate them with commas.
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To solve the equation \( 2y^{2} + 11y + 5 = (y + 5)^{2} \), we first expand the right-hand side: \[ (y + 5)^{2} = y^{2} + 10y + 25 \] Now we have the equation: \[ 2y^{2} + 11y + 5 = y^{2} + 10y + 25 \] Next, we can rearrange and combine like terms by moving everything to one side of the equation: \[ 2y^{2} + 11y + 5 - y^{2} - 10y - 25 = 0 \] This simplifies to: \[ y^{2} + y - 20 = 0 \] Now we can factor the quadratic equation: \[ (y + 5)(y - 4) = 0 \] Setting each factor equal to zero gives us the solutions: \[ y + 5 = 0 \quad \Rightarrow \quad y = -5 \] \[ y - 4 = 0 \quad \Rightarrow \quad y = 4 \] Thus, the solutions to the equation are: \[ y = -5, 4 \]